Biodegradable ceramic materials for orthopedic and dentistry applications - Mahmoud, E. M.; Sayed, M.; Mansour, T. S.; Naga, S. M. (Discover applied sciences, 2025)
From the standpoint of tissue engineering and biology, synthesizing bioceramic materials for implants and devices that promote bone regeneration is a significant challenge. Degradable materials for bone repair and regeneration are actively sought after, and it is the subject of much attention in the bioceramic materials research field, because of their biodegradable nature, which enables patients to avoid a second operation with lower pain and cost. This review article represents an overview of the most significant biodegradable ceramic materials used in orthopedic and dental applications. In addition, it discusses and summarizes the considerable advancements in the use of biodegradable ceramic materials for bone replacement as the perfect choice for orthopedic and maxillofacial applications. Additionally, it highlights the causes of biodegradability, together with an overview of traditional and modern research. It defines various biodegradable ceramic materials, their bioactivity, clinical applications, advantages, limitations, fabrication techniques, mechanical and physical characteristics, and the criteria for selecting long-lasting implant devices for bioceramic biodegradable materials. The article stated that there is still a vital need to develop a range of improved biomaterials and their manufacturing approaches. For this purpose, biodegradable materials, including polymers, ceramics, magnesium alloys and their composites, should be intensely studied as materials for repair and applications, either alone or as a coating layer for implants.